MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DENGAN MENGGUNAKAN METODE EKSPERIMEN DI KELAS V SD NEGERI 101823 BEKALA - Siregar, Hotma Tiolina (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2017)
The researcher aims to know the suitability of the action with the plan that has been prepared to know the extent to which the implementation of the action can produce changes in accordance with the desired. The instrument used is the test description and the observation sheet. This research is a classroom action research (PTK) using Experimental method on science subjects. Research subjects in class V SD Negeri 101823 Bekala which amounted to 25 people. Implementation of learning by using the experimental method on the subject of Magnet Style goes well. This is seen from the results of teacher observation and student activity, with the details of the observation of teacher activity cycle I is 63,5% that categorized enough into the second cycle is 76% both categorized and student observations on the first cycle is 62% that categorized enough and cycle II ie 74% are categorized well. Student learning outcomes after using the experimental learning method on the subject Magnet Style has increased.Â Key Words: Learning Outcomes, Experimental Methods